2022
DOI: 10.1111/lam.13673
|View full text |Cite
|
Sign up to set email alerts
|

Selected plant essential oils inhibit biofilm formation and luxS ‐ and pfs ‐mediated quorum sensing by Escherichia coli O157:H7

Abstract: Significance and Impact of the Study: We investigated the antibacterial, anti-biofilm and quorum sensing inhibitory properties of Thymus daenensis and Satureja hortensis essential oils against food-borne pathogen Escherichia coli O157:H7 using phenotypic and genotypic methods. Accordingly, the present study introduces T. daenensis and S. hortensis essential oils as new antimicrobial agents against E. coli O157:H7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Similarly, it has been reported that luxS and pfs deletion mutants of E. coli inhibit AI-2 production, biofilm formation, and motility ( Yang et al, 2014 ; Wang et al, 2016 ; Zuberi et al, 2017 ). Therefore, the luxS and pfs have been considered important therapeutic drug targets, and many inhibitors against luxS and pfs have been investigated ( Shivaprasad et al, 2021 ; Sharifi and Nayeri Fasaei, 2022 ). The lsr system is liable for AI-2 detection, uptake, and signal transduction in E. coli ( Pereira et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been reported that luxS and pfs deletion mutants of E. coli inhibit AI-2 production, biofilm formation, and motility ( Yang et al, 2014 ; Wang et al, 2016 ; Zuberi et al, 2017 ). Therefore, the luxS and pfs have been considered important therapeutic drug targets, and many inhibitors against luxS and pfs have been investigated ( Shivaprasad et al, 2021 ; Sharifi and Nayeri Fasaei, 2022 ). The lsr system is liable for AI-2 detection, uptake, and signal transduction in E. coli ( Pereira et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition effect of 32 to 256 μg/mL concentrations of synthesized AuNFs on the biofilm of the three bacterial strains tested was determined by a 96-well microplate assay as previously described [ 103 , 104 ]. Briefly, bacterial strains were inoculated in Trypticase Soy Broth (TSB) with 2 % glucose and incubated overnight at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Then, 100 µL of AuNFs (three wells for each concentration) at different concentrations (MIC to 1/16 MIC) were added into the wells of a 96-well microtiter plate and the plates were incubated further at 37 °C for 24 h. Wells containing bacterial strains and TSB were used as negative controls. The biofilm viability was measured following the previous evaluation protocol [ 103 , 104 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to investigate the MBC value, 10 μL from wells showing no visible in the microdilution broth test was inoculated onto tryptone soya agar (TSA). The MBC value was defined as the minimum concentration of the compound required to kill 99.9% of the bacteria [70]. These tests were performed in triplicate.…”
Section: The Microdiluition Broth Assaymentioning
confidence: 99%